How laypersons consider differences in sources' trustworthiness and expertise in their regulation and resolution of scientific conflicts. Issue 4 (1st October 2020) - Gottschling, Steffen; Kammerer, Yvonne; Thomm, Eva; Gerjets, Peter
ABSTRACT: When reading scientific information on the Internet laypersons frequently encounter conflicting claims. However, they usually lack the ability to resolve these scientific conflicts based on their own prior knowledge. This study aims to investigate how differences in the trustworthiness and/or expertise of the sources putting forward the conflicting claims affect laypersons' explanation and resolution of the scientific conflict. We sequentially presented 144 participants with two conflicting scientific claims regarding the safety of nanoparticles in sunscreen and manipulated whether the scientists putting forward the claims differed in their trustworthiness and/or expertise. After having read the claims on a computer in a self-paced manner, participants rated their subjective explanations for the conﬂicting claims, assessed their personal claim agreement, and completed a source memory task. We examined how differences in source trustworthiness and source expertise affected these measures. Results showed that trustworthiness differences resulted in higher attribution of the conflict to motivational explanations, and expertise differences in higher attribution of the conflict to competence explanations, than without respective differences. Furthermore, main effects of trustworthiness differences and of expertise differences on readers' claim agreement were shown, with participants agreeing more with claims from sources of higher trustworthiness or expertise.